Sifat Kimia pada Tiga Jenis Kayu Meranti Merah Kurang Dikenal - , ROHMATUS RIZQY KISNA YUNANTA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wood undoubtedly is one the important materials for human. However, its supply is declining and it is making the unbalanced supply and demand. One way to overcome that condition is searching for timber alternatives. The lesser known species that has potentiality are from red meranti group. For example, Shorea retusa (SR), Shorea macroptera (ST), and Shorea macrophylla (SP). The data containing the characteristics of red meranti wood is still limited, thus the research to determine the basic properties of those timber is necessary. So that, the proper use of those woods could be achieved. The objection of this study is to examine their chemical properties on radial and axial direction. The trees used in this research were S. retusa, and S. macroptera from PT. Hutan Sanggam Labanan Lestari, Berau, East Kalimantan, and S. macrophylla from PT. Sari Bumi Kusuma, Seruyan, Central Kalimantan. The disc samples were Â±10 cm in thickness, taken from the base and top parts of the tree. For radial direction, the disc was divided into 3 parts, the inner heartwood, outer heartwood, and sapwood. From each section, the woods were sized in 60-80 mesh powder for chemical analysis. The chemical properties tested were ethanol-toluene soluble (ETS), cold water soluble (CWS), hot water soluble (HWS), holocellulose, alfacellulose, lignin, solubility in NaOH 1%, ash contents, and pH value. The results of the research were ethanol-toluene soluble, cold water soluble, and hot water soluble are 1.47%-16.09%, 1.37%-6.91%, and 1.55%-8.14% respectively. The contents of holocellulose, alfacellulose, and lignin are 63.16%-75.16%, 39.70%-48.33%, and 24.35%- 35.95% respectively. Solubility in NaOH 1%, ash content, and pH value are 19.33%-39.56%, 0.02%-1.40%, and 4.59-8.39 respectively. SR shows the highest levels in alfacellulose, lignin, and pH values. ST give the highest values in ETS, CWS, HWS, and solubility in NaOH 1%. The SP give the highest levels in holocellulose and ash content. Holocellulose and ash content increases from heartwood to sapwood in radial direction. ETS, HWS, holocellulose, lignin, and solubility in NaOH 1% contents increases from the base to the top parts in axial direction.